On Rainbow Antimagic Coloring of Joint Product of Graphs - Brian Juned Septory; Liliek Susilowati; Dafik Dafik; M. Venkatachalam (Mathematics Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Let be a connected graph with vertex set and edge set . A bijection from to the set is a labeling of graph . The bijection is called rainbow antimagic vertex labeling if for any two edge and in path , where and . Rainbow antimagic coloring is a graph which has a rainbow antimagic labeling. Thus, every rainbow antimagic labeling induces a rainbow coloring G where the edge weight is the color of the edge . The rainbow antimagic connection number of graph is the smallest number of colors of all rainbow antimagic colorings of graph , denoted by . In this study, we studied rainbow antimagic coloring and have an exact value of rainbow antimagic connection number of joint product of graph where is graph , graph , graph , graph and graph .